Squid Ink Polysaccharides Protect Human Fibroblast Against Oxidative Stress by Regulating NADPH Oxidase and Connexin43 - Ying Chen; Ying Chen; Huazhong Liu; Hao Huang; Yuetang Ma; Ruihua Wang; Yong Hu; Xiufen Zheng; Chunmei Chen; Hongfeng Tang (Frontiers Media S.A., 2020)
Oxidation injury to skin is one of the main reasons for skin aging. The aim of the present study was to explore the protective effect of squid ink polysaccharides and its mechanism of action against H2O2-induced dermal fibroblast damage. Our results show that squid ink polysaccharides effectively reduce the fibroblast oxidative damage mediated by the up-regulation of NADPH oxidase and Connexin43. Concurrently, squid ink polysaccharides decrease the ROS induced up-regulation of MMP1 and MMP9 to decrease MMP-mediated skin aging. Therefore, we hypothesize that squid ink polysaccharides play an antioxidant role by inhibiting the expression of NADPH oxidase and connexin43. This provides a new target for the effective clinical prevention and treatment of oxidative skin damage.